Key concepts in literary theory - Wolfreys, Julian, 1958-; Womack, Kenneth; Robbins, Ruth, 1965- ([Key concepts in literature], 2014)
Key Concepts in Literary Theory presents the student of literary and critical studies with a broad range of accessible, precise and authoritative definitions of the most significant terms and concepts currently used in psychoanalytic, poststructuralist, Marxist, feminist, and postcolonial literary studies. The volume also provides clear and useful discussions of the main areas of literary, critical and cultural theory, supported by bibliographies and an expanded chronology of major thinkers. Accompanying the chronology are short biographies of major works by each critic or theorist. A must-have guide for students wishing to improve their writing skills. Updates for this 3rd edition include:. more than 100 additional terms and concepts defined addition in particular of new keywords from the social sciences, cultural studies and psychoanalysis and a broader selection of classical rhetorical terms an expanded chronology, with additional entries and a broader historical and cultural range expanded bibliographies including key texts by major critics.